Tap 'n' charge: RFID security charging hub - De Villar, Vince Anfernee C.; Molina, Atasha Rich V.; Mondero, Jairo B. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2